Analysis of Effect of Knowledge, Attitude, and Motivation on Performance of Village Midwives in Deli Serdang Regency - Fahnidar Rahmah; Juanita Juanita; R. Kintoko Rochadi (Budapest International Research and Critics University, 2022)
This study aims to analyze of effect of knowledge, attitude, and motivation on performance of village midwives in Deli Serdang Regency. This study uses quantitative research methods of analytic research using cross sectional research design. The population in this study is village midwives who served in 3 Public Health Centers in Deli Serdang Regency, Araskabu Public Health Center as many as 6 people, Pagar Merbau Public Health Center as many as 14 people, and Galang Public Health Center as many as 20 people, then the population totaling 40 people. This research sample uses a total sampling method of 40 people. Data analysis in this study uses bivariate analysis. The results show that there is effect knowledge on performance of village midwives in Deli Serdang Regency. There is effect attitude on performance of village midwives in Deli Serdang Regency. There is effect motivation on performance of village midwives in Deli Serdang Regency.